2022
DOI: 10.1111/acer.14765
|View full text |Cite
|
Sign up to set email alerts
|

Abstinence versus moderation recovery pathways following resolution of a substance use problem: Prevalence, predictors, and relationship to psychosocial well‐being in a U.S. national sample

Abstract: Background: Many people who report resolving an alcohol or other drug (AOD) problem continue some level of substance use. Little information exists, however, regarding the prevalence of this resolution pathway, or how continued substance use after resolving an AOD problem, relative to abstinence, relates to functioning, quality of life, and happiness (i.e., well-being). Greater knowledge of the prevalence and correlates of non-abstinent AOD problem resolution could inform public health messaging and clinical g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…These results support previous studies on individuals with substance use and GDs, which have reported a negative association between PRC, depression and anxiety, but a positive association between state of recovery and higher levels of PRC (Best et al, 2015;Gavriel-Fried, 2018). The results related to the positive association between PRC and happiness corresponded with previous findings in substance use problems (Eddie, Bergman, Hoffman, & Kelly, 2022). Hence, the HRC-GD index can thus be used as a measurement tool which we believe has significant implications for GD treatment, particularly as it relates to assessing both obstacles and facilitators of RC for clients.…”
Section: Discussionsupporting
confidence: 91%
“…These results support previous studies on individuals with substance use and GDs, which have reported a negative association between PRC, depression and anxiety, but a positive association between state of recovery and higher levels of PRC (Best et al, 2015;Gavriel-Fried, 2018). The results related to the positive association between PRC and happiness corresponded with previous findings in substance use problems (Eddie, Bergman, Hoffman, & Kelly, 2022). Hence, the HRC-GD index can thus be used as a measurement tool which we believe has significant implications for GD treatment, particularly as it relates to assessing both obstacles and facilitators of RC for clients.…”
Section: Discussionsupporting
confidence: 91%
“…Higher RC has previously been significantly associated with employment, 23 stable housing, 23 and lower risk substance use (as compared with high risk). 22 Investments in human capital through stable housing, such as Housing First Interventions, have shown significant decreases in emergency department visits and frequency of hospitalization; however, there were no differences in substance use. 34 Existing research has also noted sex-based differences in RC growth, with predictors of growth in males being increased meaningful activities (like employment and education), whereas predictors in females were increased community involvement and improvements in overall health.…”
Section: Discussionmentioning
confidence: 99%
“…20 Baseline RC has been positively correlated with higher quality of life and sustained recovery at 1-year follow-up 21 along with a lower risk of substance use. 22 Conversely, reductions in RC have been inversely correlated with an increased number of substances used, 23 which may reflect the severity of one's substance use. Recovery capital is also compatible with other treatments such as structured therapy or medication management.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…“Moderation” is a great example of describing non‐abstinent outcomes using positive language that emphasizes abilities instead of limitations. This is particularly important when “communicating that some… may be able to resolve an AOD problem without necessarily needing to abstain completely” (Eddie et al, 2022). Of course, not all drug use results from a similar pathological process or serves the same function, and primary vs. secondary substance use may have distinct functional implications (e.g., one may be associated with positive outcomes and the other largely negative).…”
mentioning
confidence: 99%